Effects of the surrounding matrix on tree recruitment in Amazonian forest fragments - Nascimento, Henrique Eduardo Mendonça; Andrade, Ana C.S.; Camargo, José Luís Campana; Laurance, William F.; Laurance, Susan G.W.; Ribeiro, José Eduardo L.S. (Conservation Biology, 2006)
Little is known about how the surrounding modified matrix affects tree recruitment in fragmented forests. We contrasted effects of two different matrix types, Vismia- and Cecropia-dominated regrowth, on recruitment of pioneer tree species in forest fragments in central Amazonia. Our analyses were based on 22, 1-ha plots in seven experimental forest fragments ranging in size from 1 to 100 ha. By 13 to 17 years after fragmentation, the population density of pioneer trees was significantly higher in plots surrounded by Vismia regrowth than in plots surrounded by Cecropia regrowth, and the species composition and dominance of pioneers differed markedly between the two matrix types. Cecropia sciadophylla was the most abundant pioneer in fragments surrounded by Cecropia regrowth (constituting nearly 50% of all pioneer trees), whereas densities of species in Vismia-surrounded fragments were distributed more evenly. Thus the surrounding matrix had a strong influence on patterns of tree recruitment in Amazonian forest fragments. ©2006 Society for Conservation Biology.
Keywords: Forest Ecosystem; Habitat Fragmentation; Pioneer Species; Population Density; Rainforest; Regrowth; Species Conservations; Ecosystem; Environmental Protection; Physiology; Population Dynamics; Species Difference; Tree; Conservation Of Natural Resources; Ecosystem; Population Dynamics; Species Specificity; Trees; Amazonia; South America; Cecropia; Cecropia Sciadophylla; Vismia